1997
DOI: 10.2166/wst.1997.0659
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of solid and metal element distributions in urban highway stormwater

Abstract: Urban drainage from paved surfaces transports a wide gradation of solids ranging from sub-micron particles to gravel size aggregates. This study measured physical characteristics of solids transported in lateral pavement sheet flow from a heavily traveled urban roadway in Cincinnati. The physical characteristic measured was particle size which was used as a surrogate of specific surface area. Solids were sorted according to particle size distributions (PSD). Solids ranged from smaller than 1 μm to greater than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 0 publications
4
69
2
Order By: Relevance
“…20 The behavior of cadmium obtained in this study does not agree with the literature, where Cd has been commonly found in the dissolved fraction. 20,29 Actually, the partitioning of metallic elements in drainage waters is strongly influenced by the rainfall pH, the nature and amount of solids present, the solubility and pavement residence time of the element. 29 Therefore, it is believed that Curitiba produces its own distinctive mix of sediment-flakes from different sources, which could act as a potential cadmium sorbent.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…20 The behavior of cadmium obtained in this study does not agree with the literature, where Cd has been commonly found in the dissolved fraction. 20,29 Actually, the partitioning of metallic elements in drainage waters is strongly influenced by the rainfall pH, the nature and amount of solids present, the solubility and pavement residence time of the element. 29 Therefore, it is believed that Curitiba produces its own distinctive mix of sediment-flakes from different sources, which could act as a potential cadmium sorbent.…”
Section: Resultscontrasting
confidence: 99%
“…18 In opposition to the behavior described for lead, copper has been commonly found in the dissolved fraction. 20 The behavior of cadmium obtained in this study does not agree with the literature, where Cd has been commonly found in the dissolved fraction. 20,29 Actually, the partitioning of metallic elements in drainage waters is strongly influenced by the rainfall pH, the nature and amount of solids present, the solubility and pavement residence time of the element.…”
contrasting
confidence: 99%
“…It has also been observed that flow rate and duration controls both the yield (load) and size of transported solids in urban highway stormwater (Sansalone and Buchberger 1997). Therefore, influent concentration/loading may be well correlated with the particle diameter and density in the field.…”
Section: Proceedings Of Asce/ewri World Water and Environmental Resourcmentioning
confidence: 99%
“…Given that wetlands are better than ponds at capturing finer sediment with higher metal concentrations (Sansalone and Buchberger 1997) and promoting more bio/geochemical treatment processes, it was hypothesized that the wetland section would increase the overall metal treatment even more effectively than observed in the study. In the Bäckaslöv CSW, the pond alone removed a significant percentage of the metals, particularly those in particulate form (Table 4).…”
Section: Pond Vs Wetland Performancementioning
confidence: 92%